Preservice Primary Teachers' Common Errors in Solving Mathematics Literacy Problems - Pratiwi, Enditiyas; Nanna, A. Wilda Indra; Barumbun, Mardyanto (Universitas Muhammadiyah Surakarta, 2021)
Understanding the information on the problem presented in the form of pictures is not an easy task for preservice primary teachers to lead to errors. However, preservice primary teachers can also answer correctly if given a mathematical model directly. Preservice primary teachers’ errors can be determined using a process point of view in solving mathematical problems. In a qualitative context, this study describes and analyzes the mistakes of preservice primary teachers traced through errors in solving mathematical literacy problems. This research is qualitative research, where analysis is needed to broaden the understanding of the errors that occur when solving mathematical literacy problems. The results showed that preservice primary teachers experienced errors on each indicator in four types of errors when solving mathematical literacy problems. This research found one new type of error, namely carelessness, which is an error with different types of the four types of errors that exist. Further research can be carried out by designing strategies used to improve the ability of preservice primary teachers to solve mathematical literacy problems.